2021
DOI: 10.1002/ijc.33614
|View full text |Cite
|
Sign up to set email alerts
|

Association of genomic variants at PAX8 and PBX2 with cervical cancer risk

Abstract: Cervical malignancy is triggered by human papillomavirus infection but the risk for cervical cancer has a hereditary component. From a recent Genome Wide Association Study meta‐analysis, 2q14.1 (PAX8) and 6p21.32 (PBX2) have been proposed as novel cervical cancer susceptibility loci. We investigated the two main signals at these loci in an independent case‐control series of 2578 cases with cervical dysplasia or carcinoma and 1483 healthy females. We find significant associations for both variants, rs10175462 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This study not only confirmed previously known variants at the HLA locus but also identified a novel variant at genome-wide significance on 2q13 (rs10175462) near the PAX8 gene encoding the transcription factor Paired box 8 [68]. This signal replicated in the UK biobank and in the FinnGen biobank [121] as well as in a German case-control study [146] and in the transethnic meta-analysis GWAS from the Estonian Biobank, the FinnGen study, the UK Biobank and Biobank Japan (rs4849177, [122]). Two weakly correlated variants, rs4848320 and rs1110839, had been previously associated with cervical cancer in a candidate gene study of PAX8-AS1 haplotypes [147].…”
Section: Q13 (Pax8)supporting
confidence: 82%
See 2 more Smart Citations
“…This study not only confirmed previously known variants at the HLA locus but also identified a novel variant at genome-wide significance on 2q13 (rs10175462) near the PAX8 gene encoding the transcription factor Paired box 8 [68]. This signal replicated in the UK biobank and in the FinnGen biobank [121] as well as in a German case-control study [146] and in the transethnic meta-analysis GWAS from the Estonian Biobank, the FinnGen study, the UK Biobank and Biobank Japan (rs4849177, [122]). Two weakly correlated variants, rs4848320 and rs1110839, had been previously associated with cervical cancer in a candidate gene study of PAX8-AS1 haplotypes [147].…”
Section: Q13 (Pax8)supporting
confidence: 82%
“…Even where the causal variants were determined, it still remains a challenge to assign biological function to the variants and identify the causal gene(s). Attempts for fine-mapping or functional validation via chromatin conformation or eQTL analysis are only a handful so far [119,128,136,146,153,171].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated a total of 1568 samples from the German Cervigen consortium 13 , including samples that had been collected in nine German hospitals in Hannover, Wolfsburg, Jena, Erlangen, Dresden, Halle, Munich, Berlin and Bad Münder. The HPV status of the patients was available along with other clinical variables.…”
Section: Patient Materialsmentioning
confidence: 99%
“…Similarly, we can detect PAX8 upregulations in cervical cells infected with human papillomavirus (HPV) as viral proteins disrupt TP53 and RB1 functions. In a recent study, RNA analysis in cervical samples uncovered upregulation of PAX8 transcripts in HPV-positive lesions, presumed to be the main culprit behind cervical carcinoma [42]. Several studies reported PAX8 expression in adenocarcinoma, SCC, endometrioid adenocarcinoma, and adenosquamous carcinoma of the uterine cervix [13, 30-31, 38, 43-51].…”
Section: Role Of Pax8 In Cervical Carcinomamentioning
confidence: 99%